P272 Psychological burden in newly diagnosed IBD patients: Differences between Crohn's Disease and Ulcerative Colitis in early IBD. (21st January 2022) - Bernabeu, P; Cameo, J I; Gutiérrez, A; García, G; García, M F; Aguas, M; Belen, O; Zapater, P; Cabezos, P; Andreu, A; Jover, R; van-der Hofstadt, C; et al.
Abstract: Background: Psychological factors such as stress, anxiety and depression are frequently related to IBD. However, there are few studies of these factors in patients with a new diagnosis of IBD. The aim of the present study is to test the psychological burden in patients with a recent diagnosis of IBD and to check if there are differences between Crohn's disease (CD) and Ulcerative Colitis (UC). Methods: Prospective, multi-center, observational study in patients with a new diagnosis of IBD (<6 months). The patients were recruited from 4 different Spanish hospitals. Patients were evaluated using the Holmes and Rae social readjustment rating (SRRS), the hospital anxiety and depression scale (HAD), Scale of Stress Perceived by the Disease (EAE) and quality of life questionnaire for patients with inflammatory bowel disease (IBDQ). Results: We included 156 patients, 69 (44.2%) women and 87 men (55.8%); 80 (51.3%) CD and 76 (48.7%) UC, mean age 42.3 (SD 16.21) years. The sample was homogeneous between groups in relation to socio-demographic variables. In the total sample a 60.9% of the patient associated the onset of the disease with a stressful life event. Patients with CD showed a greater psychological impact on measures of anxiety, CD 48.8% - UC 25%, OR 2.8, (95% CI 1.4–5.6), depression CD 25% - UC 9.2%, OR 3.2 (95%CI 1.2–8.3) and stressful life events CD 86.3% - UC 67.1%, OR 3 (95%CI 1.3–6.8). In terms of general quality of life, 82.9% of UC patients showed high scores compared to 57.5% of CD patients, OR 0.27 (95%CI 0.13–0.58). In the IBDQ domains, CD patients had lower scores than UC patients, except in the digestive domain, where scores were similar. In the scale of perceived stress due to the disease, both groups showed elevated values (CD 86.3% - UC 80.3%). Conclusion: Patients with a recent diagnosis of CD are more emotionally affected and have a poorer quality of life at the beginning of the diagnosis when compared to patients with UC. Both have high scores in perceived stress due to the disease. They perceive the disease at diagnosis as a highly stressful life event, so this should be considered to promote interventions (perhaps disease-specific) aimed at alleviating that stress and preventing it from interfering with the course of the disease.